Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173864
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Student

Abstract: We critically engage with CHI communities emerging outside the global North (ArabHCI and AfriCHI) to explore how participation is configured and enacted within sociocultural and political contexts fundamentally different from Western societies. We contribute to recent discussions about postcolonialism and decolonization of HCI by focusing on non-Western future technology designers. Our lens was a course designed to engage Egyptian students with a local yet culturally-distant community to design applications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The attention towards accessibility is not exhausted with offering content in the language of community members, but it should also pre-explore cross-cultural meaning attributed to visual content such as images and icons as well as the way in which participants approach and consume information held in a digital environment. A possible solution to mitigate cultural distance in the adoption of technology could be the inclusion of participants in the design process [31], and indeed this resonates with previous research on ICT4D [41,75].…”
Section: 21supporting
confidence: 69%
“…The attention towards accessibility is not exhausted with offering content in the language of community members, but it should also pre-explore cross-cultural meaning attributed to visual content such as images and icons as well as the way in which participants approach and consume information held in a digital environment. A possible solution to mitigate cultural distance in the adoption of technology could be the inclusion of participants in the design process [31], and indeed this resonates with previous research on ICT4D [41,75].…”
Section: 21supporting
confidence: 69%
“…(Höök et al, 2016). (Strohmayer et al, 2018;Lyle et al, 2018;Knouf, 2009;Giglitto et al, 2018;Linehan and Kirman, 2014;Wong-Villacres et al, 2020;Elsden et al, 2016;Knowles et al, 2014;Cutrell, 2011;Wolters et al, 2017;Shapiro, 1994;Nelimarkka, 2008;Latulipe, 2013;Howard and Irani, 2019;Preston, 1998;Ahmed et al, 2018;Allen, 1998) (Nelimarkka, 2008) Continued on next page Keyword: democracy Technology democratisation "a communally accessible, standalone voice interface which democratizes family access to technology." (Beneteau et al, 2020) and "[for] visualization [-] to be democratized, we need to provide means for non-experts to create visualizations that allow them to engage directly with datasets.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…This is not surprising as research has shown how even during African HCI winter schools, students prefer the engineering and technical dimension of interaction design to the aspects that explore values, culture, and meaning (See. [74,100,101]). This is further complicated as society has accorded high status to engineers, technicians and artists that are deemed worthy of recognition since they often engage in extensive mental activities that require rational (and in some cases non-rational) navigation of variations and probabilities.…”
Section: African Hcimentioning
confidence: 99%
“…In Africa for example, Giglitto and colleagues reported the saviourism attitude of some engineering students toward the conditions of sociability in Egyptian communities [74]. The specific mindset of the student is that of having the expertise and knowledge to fix the social world, thus conceiving design thinking as an instrument that exists within an Enlightened and agential subject.…”
Section: Saviourism Of Alternative To Postcolonialitymentioning
confidence: 99%